OBJECTIVE TESTS IN ACCOUNTING. - Graff, F. W. (The Accounting Review, 1933)
In the June 1930 issue of the journal "The Accounting Review," there was published a series of short tests in accounting theory and practices, which had been developed at the University of Minnesota. Somewhat later, in March 1931, the journal carried a series of first-year examinations which had been given at the University of Illinois. In this article two sets of examination questions in first-year accounting are presented which have been developed and used at Cleveland College of Western Reserve University. These examination questions are again of the objective type, and they may be of interest in that they reveal further possibilities of using this type of test. Some of the questions included in the first set are, how should accounts ordinarily be arranged in the general ledger, what do the equities shown by the liability column of a balance sheet represent ordinarily, what is a balance sheet intended to show, what is meant by double entry, what does a debit mean in modern accounting and how should assets be listed in a balance sheet.